2016
DOI: 10.18006/2016.4(3s).249.265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morinda citrifolia in growth, production and immunomodulatory properties in livestock and poultry: a review

Abstract: KEYWORDS Morinda citrifolia Livestock Poultry Growth Production Immunomodulatory Properties ABSTRACTMorinda citrifolia L. is commonly known as Noni and has been found to have wide range of medicinal properties. It is usually found in the coastal region in many countries including Andaman and Nicobar Islands and belongs to the family Rubiaceae. This small evergreen tree is widely grown and well adapted to the tropics and can grow in fertile, acidic, alkaline and saline affected soils. It tolerates high soil sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 119 publications
1
8
0
Order By: Relevance
“…Among the different effects that result from consumption of noni fruit juice and its derivatives, those related to cancer and immunomodulation are probably the best known. In accordance with our data, previous studies have shown that noni fruit juice consumption modulates immune responses in vivo and in vitro through the suppression of IL-4 production (Hirazumi & Furusawa, 1999;Hirazumi, Furusawa, Chou, & Hokama, 1994;Palu et al, 2008;Sunder, Sujatha, & Kundu, 2016) and the induction of IFN-γ, TNF, IL-1ß, IL-10 and IL-12 production (Hirazumi & Furusawa, 1999;Palu et al, 2008). Additionally, our data indicated that noni fruit juice consumption produces varying effects on the modulation of IL-23, IL-10, IL-4 and IL-12 in different organs, with opposite trends observed in the intestine and liver for the modulation of IL-4 and IL-10.…”
Section: Discussionsupporting
confidence: 92%
“…Among the different effects that result from consumption of noni fruit juice and its derivatives, those related to cancer and immunomodulation are probably the best known. In accordance with our data, previous studies have shown that noni fruit juice consumption modulates immune responses in vivo and in vitro through the suppression of IL-4 production (Hirazumi & Furusawa, 1999;Hirazumi, Furusawa, Chou, & Hokama, 1994;Palu et al, 2008;Sunder, Sujatha, & Kundu, 2016) and the induction of IFN-γ, TNF, IL-1ß, IL-10 and IL-12 production (Hirazumi & Furusawa, 1999;Palu et al, 2008). Additionally, our data indicated that noni fruit juice consumption produces varying effects on the modulation of IL-23, IL-10, IL-4 and IL-12 in different organs, with opposite trends observed in the intestine and liver for the modulation of IL-4 and IL-10.…”
Section: Discussionsupporting
confidence: 92%
“…Each chamber was composed of 2 pens (20 bird/pen) with their own feeder and water line. Each pen was given one of two diets: starter corn-soy based diet (Control, 3.9 Mcal ME Kg −1 and 21% CP), or control diet supplemented with 0.2% dried Noni plant (Noni, 3.9 Mcal ME Kg −1 , 19.8% CP), a commonly incorporated levels by poultry producers in tropical regions (Sunder and Kundu, 2016 ). Chicks were given ad libitum access to feed and clean water.…”
Section: Methodsmentioning
confidence: 99%
“…Also, P. guajava, a plant of great application in the treatment of the diarrheic syndrome in pigs (mainly the leaves), has hypoglycemic, antioxidant, and antiinflammatory properties due to the presence of flavonoids (mainly gammapirons) and triterpenoids [8], and also its application as a medicinal drug in the diets of mice showed an antidiabetic effect [9]. Moreover, M. citrifolia is rich in alkaloids in its leaves and fruits, which can be recommended mainly for more than 20 illnesses to human and animals, due to its antioxidant, antimicrobial immunestimulant properties [10]; specifically, in birds, Sunder et al [11] have demonstrated that daily use of this plant in the diets of laying hens increases the egg weight and shell thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In these three plants, separately, their effects have been investigated in animals of zootechnical interest with good results, mainly as nutraceutical supplements [9,11,12]. However, little is known about the use of these plants when they are mixed and supplemented or are included as powder in diets for broiler chickens.…”
Section: Introductionmentioning
confidence: 99%